2020
DOI: 10.1371/journal.pone.0239334
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of multimorbidity among adults in Botswana: A cross-sectional study

Abstract: Background Botswana is currently undergoing rapid epidemiological transition indicated by a decline in infectious diseases and an increase in chronic non-communicable diseases and their associated risk factors. The main aim of this study was to assess prevalence and correlates of multimorbidity among the adult population in Botswana. Methods A cross-sectional study called Chronic Non-Communicable Diseases Study (NCDs study) was conducted in March, 2016. Using multistage cross sectional sampling design, 1178 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 23 publications
7
40
2
2
Order By: Relevance
“…The previous study found a lack of physical activity among women who belonged to the middle to higher household income and had a higher prevalence of metabolic syndrome that further lead to multimorbidity [20]. The present study also found that ever married were having a higher prevalence of the multimorbidity compared to never-married women [24]. A crosscountry study using SAGE database found Ghana, India, South Africa, and Spain also support the present study findings [5,21].…”
Section: Discussionsupporting
confidence: 85%
“…The previous study found a lack of physical activity among women who belonged to the middle to higher household income and had a higher prevalence of metabolic syndrome that further lead to multimorbidity [20]. The present study also found that ever married were having a higher prevalence of the multimorbidity compared to never-married women [24]. A crosscountry study using SAGE database found Ghana, India, South Africa, and Spain also support the present study findings [5,21].…”
Section: Discussionsupporting
confidence: 85%
“…Heart diseases, Asthma, Goitre or any other Thyroid disorder, Cancer, Hypertension, and diabetes, etc. are the most common non-communicable diseases that contribute to the major prevalence of multimorbidity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cross-country study showed that 4.2% of all disability-adjusted life years (DALYs) were attributed to the use of alcohol, and 1.3% of all DALYs were attributed to the use of drugs [ 15 ]. Tobacco and alcohol use disorder were found to be significantly associated with multimorbid conditions among individuals [ 6 , 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-country study showed that 4.2% of all disability-adjusted life years (DALYs) were attributed to the use of alcohol, and 1.3% of all DALYs were attributed to the use of drugs [15]. Tobacco and alcohol use disorder were found to be significantly associated with multimorbid conditions among individuals [6,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%